2016
DOI: 10.1111/1477-8947.12111
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to climate variability and change in rural Kenya: farmer perceptions, strategies and climate trends

Abstract: Climate change has had a significant impact on rain-fed agricultural production in developing countries. Smallholder farmers are the most vulnerable, and currently must make production decisions in a high risk and uncertain environment with regard to rainfall and temperature. This paper uses climate and household survey data to analyse farmer perceptions regarding climate change, adaptation measures taken in response to these changes, and how well these perceptions correlate with meteorological data in Kenya. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 37 publications
11
24
0
1
Order By: Relevance
“…Additionally, they are consistent with the study of Amir et al., 2020a , Amir et al., 2020b where 96% of the farmers interviewed reported to have perceived changes in climate. Furthermore, they are in line with the findings of Ochieng et al., (2017) , Mutunga et al., (2017) and Belay et al., (2017) who reported that farmers had perceived a decrease in rainfall in their respective study areas within Kenya over time.
Figure 4 Trend of the total annual rainfall amounts received in Masaba Sub-county.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, they are consistent with the study of Amir et al., 2020a , Amir et al., 2020b where 96% of the farmers interviewed reported to have perceived changes in climate. Furthermore, they are in line with the findings of Ochieng et al., (2017) , Mutunga et al., (2017) and Belay et al., (2017) who reported that farmers had perceived a decrease in rainfall in their respective study areas within Kenya over time.
Figure 4 Trend of the total annual rainfall amounts received in Masaba Sub-county.
…”
Section: Resultssupporting
confidence: 90%
“…The smallholder farmers claimed the increase in temperature had resulted in the drying of some crops in some seasons. The findings on the perceived temperature and rainfall properties are consistent with those of Ochieng et al., (2017) who found that 74.9% of the respondents sampled from various zones of Kenya perceived an increase in temperature and 46.5% believed the rainfall has decreased over 30 years. They are equally consistent with those of Mutunga et al., (2017) who reported that 97 % to 100% of the respondents had identified a decrease in the amount of rainfall received over time.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Both responsibilities are based on the belief that climate change was already happening and most adaptation statements are confirmed by end-users, including the use of drought-resistant crops, efficient use of water, a change in cultivation patterns, relocation of crops varieties, and effective use of fertilizers and pesticides [86]. According to Ochieng et al [87] and Kibue et al [88], the type of adaptation can be divided into different issues. Firstly, changing cropping practices (introduction of new varieties, changing planting dates).…”
Section: Mitigation and Adaptation Measuresmentioning
confidence: 99%
“…Majority of smallholder farmers in Kenya depend on agriculture for survival [12]. Building their adaptive capacity and resilience to climate change is key to enable them protect their livelihoods and ensuring their food security.…”
Section: Introductionmentioning
confidence: 99%